Enhanced expression of human endogenous retroviruses in new-onset type 1 diabetes: Potential pathogenetic and therapeutic implications. (3rd July 2020) - Tovo, Pier-Angelo; Rabbone, Ivana; Tinti, Davide; Galliano, Ilaria; Trada, Michela; Daprà, Valentina; Cerutti, Franco; Bergallo, Massimiliano
Abstract: Human endogenous retroviruses (HERVs) have been studied and proposed as relevant cofactors in several autoimmune diseases, including type 1 diabetes (T1D), though with controversial results and no study at disease onset. In order to gather further information on the potential role of HERVs in the development of T1D we assessed the transcription levels of pol genes of HERV-H, HERV-K, and HERV-W in peripheral leucocytes from 37 children and adolescents with new-onset T1D and 50 age-matched control subjects. A PCR real time Taqman amplification assay was used to evaluate HERV transcripts with normalisation of the results to glyceraldehyde-3-phosphate dehydrogenase. The expression levels of HERV-H-pol gene and HERV-W-pol gene were significantly higher in diabetic patients than in control subjects. Conversely, no significant difference emerged in the expression levels of HERV-K-pol gene between diabetic patients and controls. The activation of HERV-H and HERV-W in new-onset T1D suggests their importance in the pathogenesis of the disease and supports targeted therapeutic attempts to hinder their activation.